POTENTIAL EFFECTS OF PISA-TYPE MATHEMATICAL ASSESSMENT - Azriah Azriah; Heri Retnawati; Elly Arliani (Jurnal Pedagogi Matematika, 2023)
Assessment has an important role in the learning process. Assessment is not only used to see the results of students' learning achievements but is also used to improve the learning process. PISA (Program for International Assessment) is a study of international level assessment organized by the OECD (Organization for Economic Cooperation and Development). Indonesia is one of the participating countries in the PISA study. However, the content of the questions within the PISA framework is still relatively small in the available teaching materials. So educators in Indonesia have begun to make adjustments and conduct research on the development of PISA-type assessments. The purpose of this article is to examine the PISA type of mathematical assessment that has been developed. Then, the potential effects of the problems that have been developed will be seen. This study uses the literature review method by reviewing and reviewing articles on PISA-type mathematical assessments. Article collection was carried out on Google Scholar and Research Gate in the period 2015-2021. Based on the results of the research that has been reviewed, it is known that the potential effects of the developed PISA type of mathematical assessment include problem-solving, mathematical literacy, communication skills, and reasoning abilities.